A commentary on: 'Broken silent and in hiding: tamed endogenous pararetroviruses escape elimination from the genome of sugar beet (Beta vulgaris)'. (5th August 2021) - Kovarik, Ales; Hemleben, Vera
Abstract : This article comments on: Nicola Schmidt, Kathrin M. Seibt, Beatrice Weber, Trude Schwarzacher, Thomas Schmidt, and Tony Heitkam, Broken, silent, and in hiding: tamed endogenous pararetroviruses escape elimination from the genome of sugar beet ( Beta vulgaris ), Annals of Botany Volume 128, Issue 3, 26 August 2021, Pages 281–291, https://doi.org/10.1093/aob/mcab042